Pengaruh Penggunaan Model Pembelajaran Blended Learning dan Gaya Belajar terhadap Hasil Belajar siswa Kelas X SMK 17 Agustus 1945 Surabaya - Utama, Dikey Putra (Universitas Dr. Soetomo, 2019)
Abstract The purpose of this research are 1) to describe the difference of learning study result on blended learning model based edmodo between visual, auditorial, and kinesthetic learning style on trigonometric at SMK 17 August 1945. 2) Describing differences of learning study result in the learning model without blended learning between visual, auditorial, and kinesthetic learning styles on trigonometric subjects at SMK 17 August 1945. 3) Describing differences of learning study result between blended learning models based edmodo and learning models without blended learning in terms of visual learning styles on trigonometric at SMK 17 August 1945. 4) Describing differences of learning study result between blended learning models based edmodo and learning models without blended learning in terms of auditorial learning styles on trigonometric at SMK 17 August 1945. 5) Describing differences of learning study result between blended learning models based edmodo and learning models without blended learning in terms of kinesthetic learning styles on trigonometric at SMK 17 August 1945. 6) Describing differences of learning study result between blended learning models based edmodo and learning models without blended learning in terms of learning styles on trigonometric at SMK 17 August 1945.This research is a quantitative research with quasi experimental approach (quasi experimental). Location of research at SMK 17 August 1945 Surabaya. Members of the population of 188 students. The sampling technique using simple random sampling. Samples taken as many as 60 students. Technique of collecting data using observation, questionnaire and test result learn. Data analysis techniques used independent sample t test (t test), one way anova (F test) and multivariate analysis of variance (Manova). Based on the results of data analysis, can be obtained conclusion from the results of research as follows. There are difference of learning study result on blended learning model based edmodo between visual, auditorial, and kinesthetic learning style show by the results of hypothesis testing of sig values. or a probability of . There are differences of learning study result in the learning model without blended learning between visual, auditorial, and kinesthetic learning styles show by the results of hypothesis testing with sig values. or the probability is There are differences of learning study result between blended learning models based edmodo and learning models without blended learning in terms of visual, auditorial, and kinesthetic learning styles shown by hypothesis testing results with sig values. or the probability is Keywords: Blended learning, learning style, study results Abstrak Tujuan penelitian ini adalah 1) Mendeskripsikan perbedaan hasil belajar siswa pada model blended learning berbasis edmodo antara gaya belajar visual, auditorial, dan kinestetik pada pokok bahasan trigonometri di SMK 17 Agustus 1945. 2) Mendeskripsikan perbedaan hasil belajar siswa pada model pembelajaran tanpa blended learning antara gaya belajar visual, auditorial, dan kinestetik pada pokok bahasan trigonometri di SMK 17 Agustus 1945. 3) Mendeskripsikan perbedaan hasil belajar siswa antara model blended learning berbasis edmodo dan model pembelajaran tanpa blended learning ditinjau dari gaya belajar visual pada pokok bahasan trigonometri di SMK 17 Agustus 1945. 4) Mendeskripsikan perbedaan hasil belajar siswa antara model blended learning berbasis edmodo dan model pembelajaran tanpa blended learning ditinjau dari gaya belajar auditorial pada pokok bahasan trigonometri di SMK 17 Agustus 1945. 5) Mendeskripsikan perbedaan hasil belajar siswa antara model blended learning berbasis edmodo dan model pembelajaran tanpa blended learning ditinjau dari gaya belajar kinestetik pada pokok bahasan trigonometri di SMK 17 Agustus 1945. 6) Mendeskripsikan perbedaan hasil belajar siswa antara model blended learning berbasis edmodo dan model pembelajaran tanpa blended learning ditinjau dari gaya belajar pada pokok bahasan trigonometri di SMK 17 Agustus 1945. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan eksperimen semu (quasi eksperimental). Lokasi penelitian di SMK 17 Agustus 1945 Surabaya. Anggota populasi sebanyak 188 siswa. Teknik pengambilan sampel menggunakan simple random sampling. Sampel yang diambil sebanyak 60 siswa. Teknik pengumpulan data menggunakan obseravasi, kuesioner (angket) dan tes hasil belajar. Teknik analisis data menggunakan analisis independent sample t test (uji t), one way anova (uji F) dan multivariate analysis of varians (Manova). Berdasarkan hasil analisis data, dapat diperoleh simpulan dari hasil penelitian sebagai berikut. Ada perbedaan hasil belajar siswa pada model blended learning berbasis edmodo antara gaya belajar visual, auditorial, dan kinestetik yang ditunjukkan oleh hasil pengujian hipotesis nilai sig. atau probabilitas sebesar . Ada perbedaan hasil belajar siswa pada model tanpa blended learning berbasis edmodo antara gaya belajar visual, auditorial, dan kinestetik yang ditunjukkan oleh hasil pengujian hipotesis dengan nilai sig. atau probabilitas adalah . Ada perbedaan hasil belajar siswa antara model blended learning berbasis edmodo dan model pembelajaran tanpa blended learning ditinjau dari gaya belajar visual, auditorial, maupun kinestetik yang ditunjukkan oleh hasil pengujian hipotesis dengan nilai sig. atau probabilitas adalah . Kata Kunci : Blended learning, gaya belajar, hasil belajar.